2022
DOI: 10.1155/2022/1948657
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Radiosensitizing Effect of Celastrol by Inhibiting G2/M Phase Arrest Induced by the c‐myc Gene of Human SW1353 Chondrosarcoma Cells: Network and Experimental Analyses

Abstract: Objective. Studies have unveiled that the components of Tripterygium wilfordii Hook F (TWHF) such as celastrol could attenuate apoptosis and proliferation of various tumor cells. This study is focused on the radiosensitization effect and apoptotic pathways of celastrol via the inhibition of the c-myc gene and the influence of which combined with radiotherapy on the proliferation, apoptosis, invasion, and metastasis of chondrosarcoma cells. Methods. A variety of bioinformatic tools were applied to explore the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Cells exert variations in radiosensitivity at different phases of cell-cycle making G2/M phase the most radiosensitive of them (Otani et al, 2016). Accordingly, radiosensitizers tend to arrest the cell-cycle at G2/M phase by activating cell-cycle checkpoint regulators (Morgan et al, 2015;Huang et al, 2020;Qian et al, 2022, El-Benhawy et al, 2021. But in case of radioresistant cells, these checkpoint regulators are either inactive or too deregulated thereby escape arrest and subsequent cell death (Visconti et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Cells exert variations in radiosensitivity at different phases of cell-cycle making G2/M phase the most radiosensitive of them (Otani et al, 2016). Accordingly, radiosensitizers tend to arrest the cell-cycle at G2/M phase by activating cell-cycle checkpoint regulators (Morgan et al, 2015;Huang et al, 2020;Qian et al, 2022, El-Benhawy et al, 2021. But in case of radioresistant cells, these checkpoint regulators are either inactive or too deregulated thereby escape arrest and subsequent cell death (Visconti et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%